2023
DOI: 10.3758/s13428-023-02101-9
|View full text |Cite
|
Sign up to set email alerts
|

Web-based psychoacoustics: Hearing screening, infrastructure, and validation

Abstract: Anonymous web-based experiments are increasingly used in many domains of behavioral research. However, online studies of auditory perception, especially of psychoacoustic phenomena pertaining to low-level sensory processing, are challenging because of limited available control of the acoustics, and the inability to perform audiometry to confirm normal-hearing status of participants. Here, we outline our approach to mitigate these challenges and validate our procedures by comparing web-based measurements to lab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…We conducted these auditory learning experiments with children online. While recent research has demonstrated that in-person findings of auditory learning and perception generally replicate in online conditions (Mok et al, 2023;Roark et al, 2021Roark et al, , 2022Zhao et al, 2022), this has not yet been tested in children. It is possible that children are much more susceptible than adults to distractions or other technological challenges posed by an online environment.…”
Section: Limitationsmentioning
confidence: 99%
“…We conducted these auditory learning experiments with children online. While recent research has demonstrated that in-person findings of auditory learning and perception generally replicate in online conditions (Mok et al, 2023;Roark et al, 2021Roark et al, , 2022Zhao et al, 2022), this has not yet been tested in children. It is possible that children are much more susceptible than adults to distractions or other technological challenges posed by an online environment.…”
Section: Limitationsmentioning
confidence: 99%
“…Accurately measuring psychoacoustic thresholds outside the confines of specialized laboratories could initiate important changes in how data is collected and would increase accessibility for basic and translational research [ 4 ]. Previous studies have shown success in comparing equivalent data collected in the lab versus remotely with acoustic hearing [ 5 , 6 , 7 , 8 , 9 ] as well as with electric hearing [ 10 , 11 , 12 , 13 ]. For instance, Lelo de Larrea-Mancera et al (2022) [ 5 ] measured performance on a battery of psychoacoustic experiments in tasks involving audibility, temporal fine structure sensitivity, spectro-temproal modulation sensitivity, and spatial release from masking from a large group of young normal-hearing listeners.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that the suprathreshold auditory processing thresholds obtained using uncalibrated, participant-owned devices in remote settings were comparable to the thresholds obtained in the laboratory with calibrated devices. Similarly, Mok et al (2021) [ 7 ] compared web-based measurements to lab-based thresholds on a range of classic psychoacoustic tasks such as fundamental frequency discrimination, gap detection, and sensitivity to interaural time and level differences, co-modulation masking release, word identification, and consonant confusion. The results revealed an excellent agreement between the thresholds collected using web-based and lab-based measurements indicating robustness in thresholds.…”
Section: Introductionmentioning
confidence: 99%